Restrictions on Hospital Referrals from Long-Term Care Homes in Madrid and COVID-19 Mortality from March to June 2020: A Systematic Review of Studies Conducted in Spain - Maria Victoria Zunzunegui; François Béland; Fernando J. García López (MDPI AG, 2023)
In March 2020, a ministerial directive issued by the Government of the Community of Madrid (CoM) in Spain included disability-based exclusion criteria and recommendations against hospital referral of patients with respiratory conditions living in long-term care homes (LTCHs). Our objective was to assess whether the hospitalization mortality ratio (HMR) is greater than unity, as would be expected had the more severe COVID-19 cases been hospitalized. Thirteen research publications were identified in this systematic review of mortality by place of death of COVID-19-diagnosed LTCH residents in Spain. In the two CoM studies, the HMRs were 0.9 (95%CI 0.8;1.1) and 0.7 (95%CI 0.5;0.9), respectively. Outside of the CoM, in 9 out of 11 studies, the reported HMRs were between 1.7 and 5, with lower 95% CI limits over one. Evaluation of the disability-based triage of LTCH residents during March-April 2020 in public hospitals in the CoM should be conducted.